An Economical Optimization Method for Active Power With Variable Droop Control Considering Frequency Regulation Costs in Integrated Energy Systems - Zang, Yuxiu; Ge, Weichun; Wang, Shunjiang; Zhao, Long; Tan, Che (Frontiers in Energy Research, 2022)
As a high proportion of clean energy is connected to the power grid, the occupancy rate of the system synchronous machine decreases, the inertia constant of the system decreases, and the difficulty of frequency adjustment continues to increase. The imbalance of frequency is mainly caused by the imbalance of active power, so the problem of frequency can be transformed into the problem of active power balance. According to the droop control principle, the concept of the equivalent unit regulating power coefficient is proposed, and the equivalent unit regulating power is determined by determining the system parameters and frequency offset. In order to reduce the frequency regulation cost in the integrated energy system, a feasible method considering the frequency regulation cost is proposed-variable droop control active power economic optimization method. First, the integrated energy system in this paper consists of carbon capture power plants, wind turbine generator system (WTGS), photovoltaic power generation system, energy storage batteries. All four types of power supply leave spare capacity to participate in frequency regulation through droop control. Secondly, the concept of the equivalent unit regulating power coefficient(equivalent coefficient) and the mathematical model of the equivalent unit regulating power coefficient of the integrated energy system are put forward. Then, within the allowable range of frequency fluctuations, considering carbon trading and ancillary service markets, and aiming at the lowest frequency regulation cost,. An economical optimal distribution method is established for active power in an integrated energy system including carbon capture power plants, wind power, photovoltaics, and energy storage. Taking a city in the north as an example, the improved moth flame algorithm is used to solve the problem. The simulation results show that the proposed model can improve the frequency regulation characteristics and reduce the frequency regulation cost.